(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Evaluating nurses’ knowledge on prevention of biological occupational harmful factors at Binh Luc District Medical Center, Ha Nam province in 2022. Research subjects and methods: Nurses working at the health center and at the community health station under the management of Binh Luc district health center in Ha Nam Province Results: The percentage of nurses who know biological occupational harmful factors is not high, only accounting for 54.3% to 68.1% with the contents of specimens, waste, and patient blood contaminated with microorganisms. The number of nurses who know the effects of biological occupational harm from hepatitis B and C virus infection is 63.8%; Covid infection is 67.2%; tuberculosis infection, HIV/AIDS (60.3%); respiratory tract damage (49.1%). 92.2% of nurses said that the measure to prevent biological occupational harm is using personal protective equipment; 52.6% think there must be continuous training and education and 48.3% think it is necessary to ensure occupational safety and hygiene. The rate of nurses gaining knowledge about harmful occupational factors is 22.4%. Conclusion: Nurses often suffer occupational harm while performing treatment, the main cause being carelessness and the patient’s reaction. Therefore, it is necessary to equip nurses with basic and necessary knowledge to prevent occupational harm.